THE RESEARCH OF BOOTSTRAP ADAPTATION DURING INITIAL GAS TURBINE ENGINE PARAMETERS PROCESSING - K. A. Sorokin (Научный вестник МГТУ ГА, 2016)
This article is dealing with the research of bootstrap adaptation during initial air-jet engine parameters processing in trend analysis. Types of bootstrap and its adaptation are shown. Optimal bootstrap variation length is chosen. Bootstrap-method is compared to active methods.